Adaptive Financial Risk Management Strategies for Startup Sustainability: A Systematic Literature Review - Fajrul Falah (Arthatama: Journal of Business Management and Accounting, 2024)
Startups face significant financial risks due to constrained capital, volatile markets, and dependency on external funding. This study employs a Systematic Literature Review (SLR) to examine existing research on financial risk management (FRM) strategies tailored to startups across industries and regions. Key risk factors identified include liquidity constraints, investment uncertainties, and regulatory challenges. The findings suggest that adaptive risk management frameworks—such as capital diversification, financial technology integration, and strategic governance—are crucial in mitigating financial vulnerabilities. Furthermore, financial literacy and managerial competency play pivotal roles in enhancing FRM effectiveness. This study contributes to the literature by presenting an evidence-based approach to optimizing startup FRM, emphasizing flexibility and proactive assessment. The research concludes with practical recommendations for startup founders, investors, and policymakers to implement robust and dynamic financial risk management strategies for long-term sustainability.